A CRITICAL REVIEW OF CONTROVERSIAL DRUGS - Soni Neha; Joshi Pravin (International Journal of Applied Ayurved Research, 2020)
Ayurveda or Indian system of medicine has described many medicinal plants in its different classics. Material medica of Ayurveda is one of the earliest pharmacopoeias starting from vedic period. A large percentage of medicinal plants used in Ayurveda are subject of contro-versy. Practices of polynomial nomenclature, vernacular nomenclature system of Sanskrit, different perceptions in various communities, vernacular equivalents are cumulative factors for controversy. Poor understanding of literature, non-availability of plant and parallel evolved knowledge system are some of the reasons attributed to it. Controversial drugs or Sandigdha Dravya is a term used for medicinal plants which are mentioned in Ayurvedic classics but their exact botanical sources are not known. So it is quite necessary to develop reliable parameters and methodologies for correct identification and standardization of dif-ferent medicinal plant sources having similar name to ensure good quality and efficacious medicinal preparations.